Distribution of 3-Isobutyl-2-methoxypyrazine across Rachis Components of Vitis vinifera Shiraz and Cabernet Sauvignon - Ross D. Sanders; Paul K. Boss; Dimitra L. Capone; Catherine M. Kidman; Emily L. Nicholson; David W. Jeffery (Australian Journal of Grape and Wine Research)
Rootstock can significantly alter the concentration of methoxypyrazines (MPs) in the bunch stem (rachis) of Vitis vinifera L. cv. Cabernet Sauvignon and Shiraz, which has implications for winemaking and wine style. The distribution of MPs across the rachis is an important consideration, but such information was not available. This study aimed to address this research question by comparing MP concentrations in different rachis components throughout grape maturation and in the absence of ambient light. Shiraz and Cabernet Sauvignon bunches were sampled throughout development, segmented into four components (peduncle, top rachis, bottom rachis, and pedicel), and 3-isobutyl-2-methoxypyrazine (IBMP) was quantified in each. For both cultivars, IBMP showed a negative correlation with grape maturity, with concentrations in pedicel at harvest being significantly higher than other rachis components. Additionally, light exclusion significantly increased IBMP concentrations in all rachis segments. The concentration of IBMP varied significantly between different rachis components. The greatest concentrations were measured in the pedicel, which also contributed the largest proportion among the components to total rachis by weight. Due to elevated IBMP concentrations in rachis and the difficulties in excluding matter other than grape from a fermentor, the presence of pedicel during fermentation could produce Shiraz and Cabernet Sauvignon wines with higher concentrations of MPs, thereby potentially increasing vegetal sensory characteristics.